Gravity - Gerritsen, Tess (Pocket Books, 1999)
Emma Watson, a brilliant research physician, has been training for the mission of a lifetime: to study living beings in space. Jack McCallum, Emma's estranged husband, has shared her dream of space travel, but a medical condition has grounded and embittered him. He must watch from the sidelines as his wife prepares for her first mission to the International Space Station. Once aboard, however, things go terribly wrong.